2018
DOI: 10.1093/neuros/nyy077
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological Changes in Patients Undergoing Treatment of Unruptured Intracranial Aneurysms

Abstract: Whereas the initial decline in neuropsychological functioning was greater for SC patients, 1 yr after treatment there was no significant difference in neuropsychological outcome among the SC, EC, and healthy control groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…Only Pietrantonio et al 17 demonstrated long-term cognitive changes favoring coiling, whereas both Caveney et al 5 and Preiss et al 18 found no significant differences in outcome measures in the long term (>12 months). Furthermore, Caveney et al 5 and Brundl et al 3 demonstrated that in the short term, endovascular patients outperformed microsurgical patients in memory and learning, executive function, and complex attention. This suggests that there may be effects of surgical intervention on neurocognition which need further elucidation.…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…Only Pietrantonio et al 17 demonstrated long-term cognitive changes favoring coiling, whereas both Caveney et al 5 and Preiss et al 18 found no significant differences in outcome measures in the long term (>12 months). Furthermore, Caveney et al 5 and Brundl et al 3 demonstrated that in the short term, endovascular patients outperformed microsurgical patients in memory and learning, executive function, and complex attention. This suggests that there may be effects of surgical intervention on neurocognition which need further elucidation.…”
Section: Resultsmentioning
confidence: 98%
“…Healthy controls most commonly outperformed patients receiving either treatment. 2,5,6,8,9,11,15,22 Thirteen of the 24 studies included demonstrated statistically significant neuropsychological outcomes favoring endovascular coiling. Proust et al 21 demonstrated outcomes favoring endovascular coiling approaching statistical significance ( P = .055) with the study possibly underpowered (n = 50).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations